Parasitization Levels of Spodoptera frugiperda Eggs (Smith) (Lepidoptera: Noctuidae) in Three Different Corn Ecosystems in East Java - Rizki Dwi Wahyuningsih; Tri Harjaka; Suputa Suputa; Y. Andi Trisyono (Jurnal Perlindungan Tanaman Indonesia, 2022)
Spodoptera frugiperda  (Lepidoptera: Noctuidae) has successfully invaded and spread to almost all provinces of Indonesia which may cause significant impacts on corn production. Local natural enemies could play an important role in managing this invasive insect, and more diverse ecosystems would benefit natural enemies. This study aimed to assess parasitization rates of S. frugiperda eggs by local egg parasitoids in three different corn ecosystems (agroforestry, rice field, and rainfed field) in East Java. Sentinel egg masses were used for this study by exposing eight-hour-old egg masses collected from the laboratory mass-rearing and left for 24 hours in corn plantations aged 7, 14, and 28 days after planting. Telenomus sp. was more abundant in the three ecosystems compared to Trichogramma sp. The egg mass parasitization varied from 15.6 to 52.5%. The number of egg masses parasitized was consistently higher in agroforestry, followed by rice fields and rainfed fields in all three different sampling times. Interestingly parasitization rates on egg masses were not different, and they ranged from 43.7 to 81.6%. These findings provide evidence on the importance of local egg parasitoids for managing S. frugiperda and some insights related to plant diversity to improving the services by these parasitoids.